Understanding the Barriers Againts Eco-Friendly Behavior - Winda Putri Diah Restya (Jurnal Ecopsy, 2022)
Over the past two decades, increased media coverage – coupled with economic incentives has substantially raised citizens’ awareness and concern about environmental sustainability, but has typically failed to induce persistent behavioral changes. The ineffectiveness may due to the fact that all this time the discussions and efforts to tackle environmental problems, research conducted, and policies made by the government are always based on non – psychological perspective, such as legal studies, economic, and policy maker perspective. Effort from psychological perspective is relatively not easy to find whereas acting sustainably itself is actually a form of behavior. Hence, this study attempt to understand the gap between awareness of environmental sustainability and individual’s actual behavior from a psychological perspective. The primary objective is to identify the barriers for individuals in implementing eco-friendly behavior. The data was obtained by using descriptive research method through semi-structured interview, non-participant observation combined with social experiment. As many as 32 respondents participated and chosen through incidental sampling technique. The research started by showing seven images that reflected environmental issues in order to do the mapping on participants’ stage of knowledge. the results showed that there is clear evidence on “awareness -behavior” gap while barriers to act environmentally such as: laziness, underestimate their behavior toward the environment, feeling powerless to do some changes, absence of reward and punishment.